Horizontal Transmission of Stress Resistance Genes Shape the Ecology of Beta- and Gamma-Proteobacteria - Kamal, Shady Mansour; Simpson, David J.; Wang, Zhiying; Gänzle, Michael; Römling, Ute (Frontiers in Microbiology, 2021)
The transmissible locus of stress tolerance (tLST) is found mainly in beta- and gamma proteobacteria and confers tolerance to elevated temperature, pressure and chlorine. This genomic island, previously referred to as transmissible locus of protein quality control (TLPQ) or locus of heat resistance (LHR) likely originates from an environmental bacterium thriving in extreme habitats, but has been widely transmitted by lateral gene transfer. Although highly conserved, the gene content on the island is subject to evolution with gene products to be present in functionally distinct sequence variants. While a number of these genes duplicate core genome genes, even more, those gene products can be highly expressed at all temperatures with their functionality to become dominant over core genome genes. In this review we will present current knowledge of the function of core tLST genes and discuss current knowledge on selection and counter-selection processes that favour maintenance of the tLST island, with frequent acquisition of gene products involved in cyclic di-GMP signalling, in different habitats from the environment to animals and plants, processed animal and plant products, man-made environments and subsequently humans. Running